Analisis Pengaruh Profitabilitas, Likuiditas, Kebijakan Dividen, Pertumbuhan Perusahaan Dan Struktur Aktiva Terhadap Struktur Modal - Ade Elsa Betavia (Universitas Negeri Padang, 2019)
The purpose of this study was to determine the effect of Profitability (ROE), Liquidity (CR), Dividend Policy (DPR), Growth (Sales Growth) , Asset Structure of the Capital Structure (DER). This study population is listed manufacturing industry in Indonesia Stock Exchange in 2010-2014. The method of analysis used in this study is a quantitative method with the statistical analysis of panel data regression. Using Capital Structure as variable dependent and Profitability, Liquidity, Dividend Policy, Growth, Asset Structure as independent variables. Results of the study showed partial Probability (ROE) and Liquidity (CR) significant on the Capital Structure (DER). Dividend Policy (DPR), Growth (sales growth) and Asset Structure not influence significantly to the Capital Structure (DER). Profitability (ROE), Liquidity (CR), Dividend Policy (DPR) , Growth (Sales Growth) and Asset Structure simultaneously significant on the Capital Structure (DER).